CASH WAQF IN CONTEMPORARY ISLAMIC LAW PERSPECTIVE - Mu'is, Ahmad; Farida, Laila; Huda, Achmad Miftachul (Program Studi Manajemen Zakat dan Wakaf, 2022)
Cash waqf is new though in Islamic Social Finance and still debatable. Several Islamic scholars agree and disagree in many reasons base on Islamic laws (fiqh). In this paper aim to describe Islamic Scholars view in Islamic law from classic to modern perpective in order to understand knowledge to take explanation of some reasons in Islamic law (istinbath). This writing uses literature approach, by using some sources from classic and modern books, journal and another suitable sources then make analyzing from another scholars. The advantage of this paper will open the new view of cash waqf not only Islamic law perspective but also the impact to economic development in Islamic society. More over in Indonesia, the most muslim population of the world. The writer do hope there is sustainable action from nation policy and stake holder to follow up this new reason make economic mover become Islamic social welfare. Beside of that next research is required to accomplish it